2017
DOI: 10.1016/j.srhc.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health services utilisation by Kenyan adolescent mothers: Analysis of the Demographic Health Survey 2014

Abstract: Adolescent MHS utilisation is not optimum in Kenya. More work that includes affordable care provision, cultural re-orientation, targeted mass-media campaigns and male involvement in care need to be done with emphasis on the most disadvantaged areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 11 publications
(18 reference statements)
4
28
1
Order By: Relevance
“…In 19 studies, the relationship between maternal education and overall uptake of ANC was reported. The lack of formal education and lower educational levels were predictors of poor ANC use among women in these studies in 19 of the studies 9 25 46 47 49–51 53 58–68. However, one of the studies found that more educated women were less likely to use ANC from skilled medical providers23 (table 2).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…In 19 studies, the relationship between maternal education and overall uptake of ANC was reported. The lack of formal education and lower educational levels were predictors of poor ANC use among women in these studies in 19 of the studies 9 25 46 47 49–51 53 58–68. However, one of the studies found that more educated women were less likely to use ANC from skilled medical providers23 (table 2).…”
Section: Resultsmentioning
confidence: 75%
“…In two studies, Christians were more likely to use ANC services compared with non-Christians 54 77. Women who had no religion were less likely to attend ANC in two studies27 66 (table 2).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations